2007
DOI: 10.1002/app.27518
|View full text |Cite
|
Sign up to set email alerts
|

Water absorption properties of phosphate glass fiber‐reinforced poly‐ϵ‐caprolactone composites for craniofacial bone repair

Abstract: The moisture uptake of polymers and composites has increasing significance where these materials are specified for invasive, long-term medical applications. Here we analyze mass gain and the ensuing degradation mechanisms in phosphate glass fiber reinforced poly-e-caprolactone laminates. Specimens were manufactured using in situ polymerization of e-caprolactone around a bed of phosphate glass fibers. The latter were sized with 3-aminopropyltriethoxysilane to control the rate of modulus degradation. Fiber conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
(27 reference statements)
2
10
0
Order By: Relevance
“…The results revealed a higher strength for PCL/bone complex compared with bony humerus healed with a stainless steel implant. As such, craniofacial repair fixations appear to be a plausible application for PCL, as it has also been studied by Rudd and co-workers for the last decade [19][20][21][22][23]. In other strategies, PCL scaffolds have been reinforced with Hydroxyapatite (HA) as one of the most common and inexpensive fillers broadly used [24,25] because it provides osteoconductive properties, causes no inflammatory response, and has very low toxicity in humans [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed a higher strength for PCL/bone complex compared with bony humerus healed with a stainless steel implant. As such, craniofacial repair fixations appear to be a plausible application for PCL, as it has also been studied by Rudd and co-workers for the last decade [19][20][21][22][23]. In other strategies, PCL scaffolds have been reinforced with Hydroxyapatite (HA) as one of the most common and inexpensive fillers broadly used [24,25] because it provides osteoconductive properties, causes no inflammatory response, and has very low toxicity in humans [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, its exceptional blend-compatibility has stimulated wide research into its potential application in the biomedical field [5]. PCL blends/compounds are used in sutures, ultra-thin films for dressing cutaneous wounds [6], contraceptive and fixation devices [7,8], dentistry as root fillings [9] and pharmaceutical applications for manufacturing polymeric devices for controlled drug delivery [10]. Dosage formulations for drug delivery have received excessive attention as they can transfer drugs, genes and proteins via various administration routes, including intravenous, ocular, nasal and oral [11].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of coupling agents have been investigated in order to improve the fiber/matrix interface, characterized by IFSS measurements . A common example is 3‐aminopropyltriethoxysilane (APS), which has been used both for silica based glass as well as phosphate glass fibers (PGFs) . It was reported that APS improved the IFSS significantly for silica‐based glass conversely very little or no improvement was reported at 0.043 M concentration for PGFs .…”
Section: Introductionmentioning
confidence: 99%
“…4,[12][13][14][15][16][17][18] A common example is 3-aminopropyltriethoxysilane (APS), which has been used both for silica based glass 16 as well as phosphate glass fibers (PGFs). 12,14,17 It was reported that APS improved the IFSS significantly for silica-based glass conversely very little or no improvement was reported at 0.043M concentration for PGFs. 14 However, when APS was used at higher concentrations (1-10 wt %) within a PGF reinforced polycaprolactone (PCL) composite, the bending strength was reported to increase by 30 MPa (from 55 to 85 MPa).…”
Section: Introductionmentioning
confidence: 99%